Mesopolyploidy as a taxonomic clade marker for Brassica and relatives (tribe Brassiceae) - Thomas, Shawn K.; Abrahams, R Shawn; Kick, Daniel Robert; Walden, Nora; Conant, Gavin; McKain, Michael R; An, Hong; Arias, Tatiana; Edger, Patrick P; Harkess, Alex; Hendriks, Kasper P; Koch, Marcus; et al. (Annals of botany, 2025)
Whole-genome duplications (WGDs) are rampant in flowering plant genomes. Within Brassicaceae, the genus Brassica (including crop mustards) and relatives (tribe Brassiceae) are hypothesized to share an ancient mesohexaploidy, or whole-genome triplication (WGT), resulting from two WGD events (Br-α WGT). However, the phylogenetic boundaries of the Br-α WGT remain unknown.We use phylogenomic assessments and divergence time analyses to place and date the Br-α WGT. We see conflicting topologies among the plastid and nuclear trees putatively due to polyploidy, hybridization and reticulate evolution. Despite this, we find tribe Brassiceae to be monophyletic in both trees.As currently circumscribed, tribe Brassiceae does not share the Br-α WGT. The sister clade to the rest of the tribe, containing the genera Orychophragmus and Sinalliaria, show no evidence of the Br-α WGT. Based on this placement, divergence time analyses indicate that the Br-α WGT would have occurred between 12.1 and 10.7 million years ago.We propose a new taxonomic revision for the tribe Brassiceae based on the shared characteristics of the Br-α WGT. This presents a stable characteristic for the tribe, which was not the case in previous taxonomies based on morphological characters. These findings help clarify the history of the mustard crops and their relatives and resolve long-standing issues with the circumscription of the tribe Brassiceae.
Online verfügbar: 02. August 2025
Gesehen am 05.02.2026